Rancang Bangun Acrylic Engraver and Cutting Machine Menggunakan CNC Milling 3 Axis Berbasis Mikrokontroler - Choirony, Iklil Vurqon; Hariyanto, Mohammad Slamed; Ulum, Miftachul; Ubaidillah, Achmad; Haryanto, Haryanto; Alfita, Riza (Elektrika, 2021)
The purpose of this research is to design and implement an automatic acrylic carving and cutting tool using a microcontroller-based 3-axis CNC machine. Computer Numerical Control (CNC) is a machine technology that is operated automatically to support the demand for a product that has a complex shape and high accuracy. In general, the construction of a 3-axis CNC machine and its working system is synchronization between the computer and its mechanics. This tool has a work process by utilizing the G-Code method as a command on the machine to carry out engraving and cutting automatically. The G-code was obtained from a previously designed image and then converted using the Aspire 9.0 software. Engraving and cutting is done by sending the G-code file to the microcontroller via the Universal G-code Sender software, then the microcontroller sends a signal to drive the motor driver which then drives the stepper motor so that the actuator movement is generated according to the image in the G-code file. Simultaneously the spindle motor will be active to engrave or cut acrylic. In this study, a trial scenario was carried out to determine the precision and accuracy of the tool, namely by engraving and cutting flat shapes such as squares, circles, triangles and segments. The percentage of success generated from this tool is 97,08% to 100%. Furthermore, testing is carried out to make products in the form of engraving writing, logos and calligraphy. Apart from that, we also tested cutting letters and key chains. When the test is carried out, the accuracy level is 1mm.